2020
DOI: 10.17113/10.17113/ftb.58.03.20.6459
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of a Tropical Beverage by Applying Heat Treatment and High Hydrostatic Pressure

Abstract: Research background Passion fruit and carrot with vegetables that contain a good antioxidant capacity, however, their consumption is low. There is no information available on the use of these in beverages and with processes such as high hydrostatic pressures that allow the safety of the drink without affecting its quality. Experimental approach. In this study the effect of high hydrostatic pressures (HHP) (500 MPa, 250 s, 25 °C) and thermal processing (65 °C, 10 min; 75 °C, 2 min and 95 °C, 1 min) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Similarly, Blaszczak et al (2021) reported that HHP treatment (450, 550, or 650 MPa for 5 or 15 min) of kiwi berry fruits resulted in increases in FRAP values which also be attributed to the promoted release of polyphenols from the plant tissue by HHP treatment. These results were also in accord with those found by Marengo-Orozco et al (2020) in tropical beverages processed at 500 MPa/250 s during storage.…”
Section: Physicochemical Characteristics Antioxidant Capacity and End...supporting
confidence: 92%
“…Similarly, Blaszczak et al (2021) reported that HHP treatment (450, 550, or 650 MPa for 5 or 15 min) of kiwi berry fruits resulted in increases in FRAP values which also be attributed to the promoted release of polyphenols from the plant tissue by HHP treatment. These results were also in accord with those found by Marengo-Orozco et al (2020) in tropical beverages processed at 500 MPa/250 s during storage.…”
Section: Physicochemical Characteristics Antioxidant Capacity and End...supporting
confidence: 92%